Markers of vascular autoregulation in primary open-angle glaucoma - N.E. Fomin; A.V. Kuroyedov (РМЖ "Клиническая офтальмология")
N.E. Fomin1,2, A.V. Kuroyedov1,2 1Mandryka Central Military Clinical Hospital, Moscow, Russian Federation 2Pirogov Russian National Research Medical University, Moscow, Russian Federation Vascular endothelial growth factor, or VEGF, was discovered in 1989. VEGF is a multifunctional cytokine which provides mitogenic effects on endothelial cells and monocytes/macrophages due to the presence of surface VEGF receptors on these cells. This is the key member of VEGF family involved in angiogenesis. Normal development of vascular and nervous systems of the eye is possible in the presence of various concentrations of different VEGF isoforms only. The role of this growth factor is important not only in the early stages of eye development, but also in the adults for retinal viability  maintaining. VEGF is involved in the development of optic nerve and retinal neurons by promoting neuronal proliferation and stimulating endothelial cells. Experimental studies demonstrate that ischemia and axonotomy activate VEGF production by retinal ganglion cells. Ischemia and hypoxia of anterior and posterior eye segments as well as ischemic damage of other ocular tissues provide potential mechanism contributing to the increased VEGF expression in ocular tissues. Many studies have revealed an increase in VEGF levels in subretinal fluid, membranes, and the vitreous in patients with glaucoma. Associations of genetic polymorphisms of growth factors contributing to the development of primary open-angle glaucoma (POAG) were studied. In particular, cytokine genetic polymorphism typing was performed. It was demonstrated that VEGF (VEGFA с.—958C>T) is potentially involved in POAG pathogenesis. Therefore, it is reasonable to measure VEGF levels in aqueous humor at various stages of POAG to evaluate disease activity and to predict disease course. Keywords: primary open-angle glaucoma, intraocular pressure, vascular endothelial growth factor, VEGF, hypoxia, ischemia, markers. For citation: Fomin N.E., Kuroyedov A.V. Markers of vascular autoregulation in primary open-angle glaucoma. Russian Journal of Clinical Ophthalmology. 2019;19(4):218–223.